Mini-Refinery Vacuum Unit: Functional Analysis and Improvement of Vacuum Overhead System - Eduard Osipov (MDPI AG, 2021)
The purpose of this study was to analyze the functioning of the vacuum distillation unit of a mini-refinery and to develop recommendations for improving the vacuum overhead system with the aim to reduce the cost of creating and maintaining a vacuum in the fuel oil separation column. A calculation model of the vacuum unit was developed in the Unisim Design R451 software package, which was identified by comparing the calculated data with the data from an industrial study for two operating modes of the installation. Replacing the existing steam-ejector pump with a liquid-ring vacuum pump was proposed. A numerical experiment was carried out on the developed model, the purpose of which was to determine the “bottlenecks” of the scheme. The peculiarity of the experiment was that the vacuum column and the vacuum overhead system were considered as a single whole. As a result, it was determined that the “bottleneck” is the condenser, which was proposed to be replaced. During the technical and economic analysis, two possible vacuum overhead system schemes were considered; according to the results, it was determined that the vacuum overhead system scheme based on a liquid-ring vacuum pump will help reduce operating costs by 78%.